Analisis Perilaku Konsumsi Dalam Belanja Online Dikalangan Mahasiswa - Shasa Afriza; Isabella Magdalena Simbolon; Hezra Naumi Syariah Panjaitan; Chaterine Ratu Rebecca Sirait (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
The rapid growth of e-commerce has significantly transformed students’ consumption behavior, particularly in online shopping activities. This study aims to analyze consumption patterns among university students and identify factors influencing purchasing decisions and satisfaction in online shopping. A quantitative approach was employed using a survey method involving 26 student respondents who had experience with online shopping. Data were collected through structured questionnaires and analyzed descriptively. The results indicate that female students dominate online shopping activities, with Shopee emerging as the most frequently used platform. The frequency of online shopping among students remains within a moderate range, while fashion products constitute the most commonly purchased items. Price affordability, discounts, ease of use, and consumer reviews are identified as the primary factors influencing purchasing decisions. Although most students express a relatively high level of trust and satisfaction with online shopping, experiences of disappointment due to product mismatch or quality issues are still common. These findings suggest that online shopping has become an integral part of students’ lifestyles, yet conscious control and rational consideration are necessary to prevent excessive consumptive behavior.